2022
DOI: 10.20547/jess1022210202
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Information and Communications Technology in Teaching: Perceptions from Teachers in Malawi

Abstract: The integration of ICT in teaching and learning has taken center stage across the world. Many countries in developed and developing countries alike have adopted this integration. The integration of ICT is however dependent on the perceptions of teachers.This study aimed to find out the perception of teachers on the use of ICT in teaching and learning. Findings from this study reveal that teachers in Malawi have a negative perception in the integration of ICT in teaching and learning. The study also reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…The above signals that teachers have a negative attitude towards using technology. A negative attitude by teachers was also expressed in a study by Manjawira (2022), which revealed that teachers in Malawi have a negative perception of the integration of ICT in teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…The above signals that teachers have a negative attitude towards using technology. A negative attitude by teachers was also expressed in a study by Manjawira (2022), which revealed that teachers in Malawi have a negative perception of the integration of ICT in teaching and learning.…”
Section: Discussionmentioning
confidence: 99%